30-day Readmission After Pancreatic Resection: A Systematic Review of the Literature and Meta-analysis. Issue 2 (August 2017) - Fisher, Alexander V.; Fernandes-Taylor, Sara; Campbell-Flohr, Stephanie A.; Clarkson, Sam J.; Winslow, Emily R.; Abbott, Daniel E.; Weber, Sharon M.
Abstract : Objective: The aim of this study was to identify and compare common reasons and risk factors for 30-day readmission after pancreatic resection. Background: Hospital readmission after pancreatic resection is common and costly. Many studies have evaluated this problem and numerous discrepancies exist regarding the primary reasons and risk factors for readmission. Methods: Multiple electronic databases were searched from 2002 to 2016, and 15 relevant articles identified. Overall readmission rate was calculated from individual study estimates using a random-effects model. Study data were combined and overall estimates of odds ratios (ORs) and 95% confidence intervals (CIs) were calculated for each risk factor. Multivariable data were qualitatively synthesized. Results: The overall 30-day readmission rate was 19.1% (95% CI 17.4–20.7) across all studies. Infectious complications and gastrointestinal disorders, such as failure to thrive and delayed gastric emptying, together accounted for 58.9% of all readmissions. Demographic factors did not predict readmission. Heart disease (OR 1.37, 95% CI 1.12–1.67), hypertension (OR 1.44, 95% CI 1.09–1.91), and intraoperative blood transfusion (OR 1.45, 95% CI 1.15–1.83) were weak predictors of readmission, while any postoperative complications (OR 2.22, 95% CI 1.55–3.18) or severe complications (OR 2.84, 95% CI 1.65–4.89) were stronger predictors. Conclusions: Readmission after pancreatic resection is common and can largely be attributed to infectious complications and inability to maintain adequate hydration and nutrition. Focus on outpatient resources and follow-up to address these issues will prove valuable in reducing readmissions. Abstract : Supplemental Digital Content is available in the text